The differential cytology atypia koilocitotica - Vega Rizo Patrón, Leoncio (2015)
The authors studied 10 cases of the so-called "koilocitoticatypia" from the files of the Institute of Pathology of the Medical School of San Fernando in Loayza Hospital, Lima. Two different histological patterns of this lesion were described, which probably correspond to different phases of evolution. It was determined the cytological picture corresponding to this lesion which shows a main percentage of atypical intermediate cells, some of them with clear cytoplasmic vacuolization.